Psychosocial aspects of the usage of modern technologies in diabetes mellitus - Oleg G. Motovilin; Elena V. Surkova; Anush S. Baburyan; Lyudmila I. Ibragimova; Alexander Y. Mayorov (Сахарный диабет)
This article represents a review of trials on the relationship between the use of modern technologies in the treatment of diabetes, such as continuous subcutaneous insulin infusion (CSII) and continuous glucose monitoring (CGM), and the psychological characteristics of patients. The review includes Russian studies and foreign publications. The analysis showed that the psychological aspects of using CSII are considered more often than CGM. Most Russian authors agree that the use of technology is associated with an increased psychological well-being of patients. Foreign researchers generally agree with the same point of view but also report a weaker correlation. One of the most significant conclusions of this analysis is that the use of modern technologies itself does not guarantee an improved quality of life (QOL) and psychological well-being, but technologies such as CSII and CGM provide patients with opportunities to achieve greater effectiveness in treating diabetes, improving clinical and metabolic parameters and therefore improving QOL. However, the use of these devices, as well as many other technological tools, is associated with certain psychological problems, both in terms of their acquisition and influence on patients’ subjective well-being. Early diagnosis and prevention of such problems should be one of the tasks in preparing patients for the use of modern technologies. A positive effect on both clinical and metabolic indicators as well as on the mental sphere and social life of patients can be achieved only by combining complete training (optimally—according to specialised programmes) with medical support.